A new entity in the NARS2 variant: the first reported case of type 1 diabetes mellitus associated with the phenotype. (20th January 2023) - Cokyaman, Turgay; Cetin, Huriye; Dogan, Durmus; Silan, Fatma
Abstract: NARS2 mutations are known to cause various clinical phenotypes such as nonsyndromic hearing loss, Leigh/Alpers syndrome, refractory epilepsy, developmental delay, intellectual disability and myopathy. We presented the first Turkish variant of NASR2 and added type 1 diabetes mellitus (DM), which was not previously described in the phenotype spectrum of this disease. A 4.5-month-old girl presented with hearing loss, hypotonia, refractory myoclonic epilepsy, severe developmental delay and large subdural hemorrhage. In the first year of the follow-up, type 1 DM developed. A homozygous missense mutation, [c.500 A>G, p.H167R] in the NARS2 gene was detected in the trio-based whole-exome sequencing (WES). In this disease, in addition to multi-organ involvement, type 1 DM may also develop, as in our case. Since it is a mitochondrial disease, the decision to treat with valproic acid should be reconsidered. The long diagnostic process can be shortened with WES.